Characterization of irradiation-induced crosslink ethylene vinyl acetate/waste tire dust (EVA/WTD) blend / Anis Sakinah Zainal Abidin, Chantara Thevy Ratnam and Luqman Chuah Abdullah - Zainal Abidin, Anis Sakinah; Ratnam, Chantara Thevy; Abdullah, Luqman Chuah (2008)
The effect of irradiation on 90/10 Ethylene Vinyl Acetate/Waste Tire Dust (EVA/WTD) blend was studied. Blends of EVA/WTD were prepared by using a Haake mixer at 140°C. The blend was then irradiated by using a 3.0MeV electron beam machine at doses ranging from 50 to 200 kGy in air and room temperature. The dynamic mechanical properties, tensile properties, and gel fraction of the blends were measured. It was found that the tensile strength and modulus increased with irradiation with a concomitant decline in elongation at break. Results on gel fraction revealed that under the irradiation condition employed, the EVA/WTD blend crosslinked by electron beam irradiation. The addition of TMPTA and TPGDA was found to be effective in increasing the degree of crosslinking.